Mapping the Nexus of Etnobotany and Education: A Bibliometric Approach to Advancing 21st-Century Skills through Etnopedagogy - Yani, Ahmad; Makkatenni; Rijal, Syamsu (INSTITUT AGAMA ISLAM NEGERI AMBON, 2026)
The integration of ethnobotany and education through ethnopedagogy is increasingly acknowledged as a promising strategy to foster the development of 21st-century skills, such as critical thinking, creativity, collaboration, and cultural literacy. Nevertheless, a comprehensive mapping of the research landscape connecting these fields remains scarce. This study seeks to analyze global research trends, intellectual structures, and thematic developments in studies that link ethnobotany, education, and ethnopedagogy. A bibliometric analysis was conducted using peer-reviewed articles indexed in Scopus and Web of Science that were published between 2010 and 2025. Data were analyzed using Bibliometrix R package and VOSviewer to examine publication growth, influential authors and journals, institutional contributions, and keyword co-occurrence networks. The findings indicate a consistent increase in the number of publications over the past decade, with major research clusters focusing on indigenous knowledge systems, plant-based science education, and community-oriented pedagogical practices. Thematic evolution analysis revealed a shift from descriptive documentation of ethnobotanical knowledge to integrative educational frameworks that embed local plant knowledge within formal and informal learning contexts. Collaboration networks demonstrate increasing transnational partnerships, particularly among scholars from biodiversity-rich regions in Asia, Africa, and Latin America. Despite this progress, empirical studies evaluating the impact of ethnobotanical learning on students’ 21st-century skills remain limited. This study provides a comprehensive knowledge map and highlights future research directions to strengthen the integration of ethnopedagogy in science education. Keywords: Ethnobotany, Ethnopedagogy, Biology Education, Bibliometric Analysis, 21st-Century Skills